A Case Of Bilateral Acquired Localized Lipoatrophy - Osman Tanrıkulu; Yavuz Yesilova; Mustafa Aksoy (Karger Publishers, 2016)
Lipoatrophy is characterized by inflammation and tissue loss in fatty tissue. This disease may be congenital or acquired, primary or secondary. Secondary lipoatrophy develops with infections, collagen tissue diseases, tumors and drug injections. In this report, we present the case of a 14-year-old female patient who developed lipoatrophy following intramuscular steroid injection to both buttocks.